2002
DOI: 10.1086/339979
|View full text |Cite
|
Sign up to set email alerts
|

Low Surface Brightness Galaxies and the Tully-Fisher Relation

Abstract: We present Very Large Array (VLA) H i imaging of four low surface brightness (LSB) galaxies ([OBC97] P01-3, [OBC97] C06-1, [OBC97] C04-1, [OBC97] C04-2), 1 which were thought to strongly deviate from the Tully-Fisher (TF) relation based on Arecibo single-dish observations. We do not detect three of the four targeted low surface brightness galaxies (LSBs) in H i down to a 4 limit of 0.08 Jy km s À1 . We find that two of the four of these LSBs have bright galaxies at projected distances of 2<6 and 2<9, which hav… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 31 publications
4
25
0
Order By: Relevance
“…This study of infrared LSBs was also intended to investigate the possibility of the existence of a substantial population of red LSBs, like those reported by O'Neil et al (1997b). Although the H  study of O'Neil et al (2000) indicated that some of them did not seem to follow the "standard" Tully-Fisher relation, appearing to be severely underluminous for their total mass, observations by Chung et al (2002) indicate that their rotational properties were mismeasured due to confusion with neighbouring galaxies. An infrared-selected sample should allow us to identify whether there is a significant population of very red LSBs.…”
Section: Low Surface Brightness Galaxiesmentioning
confidence: 99%
“…This study of infrared LSBs was also intended to investigate the possibility of the existence of a substantial population of red LSBs, like those reported by O'Neil et al (1997b). Although the H  study of O'Neil et al (2000) indicated that some of them did not seem to follow the "standard" Tully-Fisher relation, appearing to be severely underluminous for their total mass, observations by Chung et al (2002) indicate that their rotational properties were mismeasured due to confusion with neighbouring galaxies. An infrared-selected sample should allow us to identify whether there is a significant population of very red LSBs.…”
Section: Low Surface Brightness Galaxiesmentioning
confidence: 99%
“…Followup studies initially indicated that these red LSBs had rapid rotational speeds exceeding 200 km s −1 and they did not seem to follow the "standard" Tully-Fisher relation, in the sense that they appeared to be severely underluminous for their total mass (O'Neil et al 2000). More recent observations by Chung et al (2002) indicate that the rotational properties of these red LSBs were mismeasured due to confusion with neighbouring galaxies. An infrared-selected sample should allow us to identify whether there is a significant population of very red LSBs.…”
Section: Low Surface Brightness Galaxiesmentioning
confidence: 99%
“…Follow-up H  line studies initially indicated that some of these red LSBs with rotational speeds exceeding 200 km s −1 did not seem to follow the "standard" Tully-Fisher relation established for HSB galaxies, in the sense that they appeared to be severely underluminous for their total mass (O'Neil et al 2000). More recent H  imaging observations by Chung et al (2002) indicate that the rotational properties and total H  mass of these red LSBs had been strongly overestimated due to confusion within the telescope beam with neighbouring galaxies. An infrared-selected sample should allow us to identify whether there is a significant population of very red LSBs.…”
Section: Introductionmentioning
confidence: 99%